Increasing Gas Production of Continuous Freeze-Thaw Hydrate Deposits Based on Local Reservoir Reconstruction - Pengfei Shen; Xiyu Mao; Chaoqun Cui; Xinwang Li; Meng Li; Li Chen; Dandan Liu (Geofluids)
The fracturing technology for increasing gas production based on hydrate reservoir reconstruction has been proven to have the application prospect of hydrate production. The main content of this work is to study the influence mechanism between multiple production wells after fracturing the reservoirs around horizontal wells. Simulation results indicated that the gas production rates and cumulative volume of released gas by using hydraulic fracturing were both higher than that by using the traditional depressurization method. The average gas-to-water ratio in this work has broken through the technical bottleneck of exploiting hydrate only by the traditional depressurization method. After the rock matrix around the horizontal well was fractured, the permeability of the reservoir in the fracturing area would be increased; thus, the propagation distance of pressure drop would be promoted. In addition, the penetration of the hydrate decomposition area between horizontal production wells was conducive to promoting the flow of decomposed gas and water to production wells. Besides, the hydraulic fracturing method to increase the permeability of the reservoir around the production well is very effective for the gas production of low-permeability natural hydrate deposits. The best distance between production wells was recommended to be 45~60 m, and it was recommended to provide appropriate heat in the area between the two wells to accelerate the decomposition of hydrate.